JOURNALISTIC CULTURE IN THE ONLINE MEDIA OF THE BANDUNG CITY GOVERMANTS PUBLIC RELATIONS - Novrizon Marzal; Mahmoed Mohamed Hosny (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The journalistic culture is currently evolving at such a quick pace that it is reflected in the public media held by the Bandung City government. Especially in the online public media, which is administered by the Bandung City government's Public Relations, such as websites, Facebook, Twitter, and Instagram. The goal of this study is to learn more about Bandung City Public Relations' journalistic culture. This study took a qualitative approach and used a qualitative descriptive method, with Kuhlthau's Information Search Behavior Theory, also known as the